The Effect of Implementation of the 2013 Curriculum on the Professional Competence of Islamic Religious Education Teachers - Ariska, Desy (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2023)
Purpose of the study The purpose of this study was to determine the implementation of the 2013 Curriculum at Public Elementary School 009 Kuala Lemang, Keritang District. To determine the professional competence of Islamic Religious Education teachers at 009 Kuala Lemang Public Elementary School, Keritang District. To determine the effect of implementing the 2013 Curriculum on the professional competence of Islamic Religious Education teachers at Public Elementary School 009 Kuala Lemang, Keritang District. Methodology: This type of research is a quantitative descriptive research. The population in this study was 1 Islamic Religious Education teacher at 009 Kuala Lemang Public Elementary School, Keritang District. The data in this study were collected using observation, interview and documentation techniques. Furthermore, the collected data was analyzed using the simple linear regression equation formula Ŷ = α + Bx. Main Findings: The results of data analysis through observation can be summarized as follows: Implementation of the 2013 Curriculum by Islamic Religious Education teachers at 009 Kuala Lemang Public Elementary School, Keritang District, reached 74.17% and was categorized as good, because the 74.17% figure lies in the 61% interval - 80%. The professional competence of Islamic Religious Education teachers at Public Elementary School 009 Kuala Lemang, Keritang District, reaches 78.10% and is categorized as good, because the 78.10% figure lies in the 61% - 80% interval. There is a positive and significant influence between the implementation of the 2013 Curriculum on the professional competence of Islamic Religious Education teachers at Public Elementary School 009 Kuala Lemang, Keritang District, as indicated by Fcount ≤ Ftable (1.419 ≤ 3.81). Novelty/Originality of this study: By conducting this research, it can be seen that the positive influence of the implementation of the 2013 curriculum on the professional competence of Islamic religious education teachers at SD Negeri 009 Kuala Lemang District.